Country Image in Advertising Discourse: Between Commercial and Social Components - E. N. Remchukova; V. A. Omelianenko (Научный диалог, 2020)
The ways of creating the country’s image in the texts of modern Russian commercial advertising, namely, such a variety, which is defined as nationally oriented advertising are discussed in the article. This type of advertising is considered as a multimodal complex, however, special attention is paid to the analysis of linguistic means that provide such advertising with a “reputation” base - it fulfills not only commercial, but also social tasks. The specificity of creating an image of the country in nationally oriented advertising by demonstrating the geographical and ethnographic features of “one’s own”, native, or “foreign” country and mythologizing “one’s own” or “foreign” national character is revealed. It is shown that the positive image of “own” country performs not only the function of promoting goods on the market, but also the function of persuasion and education. It has been established that the image of a “foreign” country ensures positioning in the domestic market of the producing country or the country with which the production tradition of the advertised product is associated. The conclusions and results of the study allow one to gain a more complete picture of the peculiarities of ethnomarketing, ways of manipulating a potential audience by appealing to national values and stereotypes, and contribute to advertology, political linguistics and linguoimagelogy.